2015
DOI: 10.1080/01419870.2015.1080381
|View full text |Cite
|
Sign up to set email alerts
|

Vietnamese migrant networks in Taiwan: the curse and boon of social capital

Abstract: Drawing on ethnographic research on Vietnamese migrant workers in Taiwan, I seek to engage with and contribute to the scholarship on migrant networks and social capital. My research demonstrates that migrant networks are central to the social life of Vietnamese workers, offering not only a vital source of material and psychological support but also a platform where relationships are developed, sustained and contested. It reveals both productive and destructive potentials of social capital in situations where t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…An empirical study regarding Brazilian immigrants’ social capital and psychological well-being confirmed that Brazilian immigrants in Japan benefited significantly from bonding social capital with their extended families in terms of improved mental health [ 13 ]. Vietnamese migrant workers’ bonding social capital in Taiwan is found to be the central to the social life of Vietnamese workers, which offered not only material but also psychological support [ 14 ]. However, there is so far no empirical research on Chinese immigrants in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…An empirical study regarding Brazilian immigrants’ social capital and psychological well-being confirmed that Brazilian immigrants in Japan benefited significantly from bonding social capital with their extended families in terms of improved mental health [ 13 ]. Vietnamese migrant workers’ bonding social capital in Taiwan is found to be the central to the social life of Vietnamese workers, which offered not only material but also psychological support [ 14 ]. However, there is so far no empirical research on Chinese immigrants in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Engagement in extramarital sex or conjugality has notably been documented in diverse contexts of male migration, both through commercial sex and through sexual relations with other migrants or locals (Liu-Farrer 2010;Thuy & Kretchmar 2008;Lang & Smart 2002;Shen 2005;Tsujimoto 2014). In the context of Vietnamese migrants in Taiwan, extramarital conjugality represents a source of support for intimate relationships while being "minefields" offering echo chambers to intimate gossips and rumours (Hoang & Yeoh 2014;Hoang 2016). The weight of social control within their homosocial or ethnic migrant network may push male migrants to strive to preserve "reputation" and thus to refrain from involving in extramarital affairs, although instances of occasional casual sex may be tolerated (Hirsch et al 2007;Thuy & Kretchmar 2008).…”
Section: Resultsmentioning
confidence: 99%
“…The mobility restrictions that are self‐imposed due to financial pressure, a deep‐rooted fear for and distrust of state authority, and weaker social networks (cf. Hoang ), among others, explain their inclination for individual and isolated acts such as running away. Lan (: 79) sees the phenomenon of ‘runaway’ as occupation specific – something that arises from the prohibitive nature of domestic workers' life.…”
Section: Resultsmentioning
confidence: 99%
“…Painstakingly, migrants carve out every little room for manoeuvre when situations permit and adjust their strategies accordingly. These everyday forms of power and resistance (Foucault, 1982;Scott, 1985) tend to prevail over more institutionalised and organised forms of power, though at a considerable cost for migrants and their families (see also Hoang andYeoh, 2012, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation